2009
DOI: 10.1037/a0015832
|View full text |Cite
|
Sign up to set email alerts
|

Competency benchmarks: A model for understanding and measuring competence in professional psychology across training levels.

Abstract: The Competency Benchmarks document outlines core foundational and functional competencies in professional psychology across three levels of professional development: readiness for practicum, readiness for internship, and readiness for entry to practice. Within each level, the document lists the essential components that comprise the core competencies and behavioral indicators that provide operational descriptions of the essential elements. This document builds on previous initiatives within professional psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
1,006
2
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(1,030 citation statements)
references
References 32 publications
14
1,006
2
8
Order By: Relevance
“…This approach is still evident in current educational practices in the field. For example, the American Psychological Association (APA) Assessment of Competency Benchmarks Work Group (Fouad et al, 2009) identified one of the "essential components" of competent practice as follows: "Formulates and conceptualizes cases and plan interventions utilizing at least one consistent theoretical orientation" (p. S19). To apply to internships listed by the Association of Psychology Postdoctoral and Internship Centers (APPIC), students need to answer the following question on the APPIC Application for Psychology Internship: "Please describe your theoretical orientation and how this influences your approach to case conceptualization and intervention" (APPIC, 2015).…”
Section: The Proliferation Of Theoretical Orientationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is still evident in current educational practices in the field. For example, the American Psychological Association (APA) Assessment of Competency Benchmarks Work Group (Fouad et al, 2009) identified one of the "essential components" of competent practice as follows: "Formulates and conceptualizes cases and plan interventions utilizing at least one consistent theoretical orientation" (p. S19). To apply to internships listed by the Association of Psychology Postdoctoral and Internship Centers (APPIC), students need to answer the following question on the APPIC Application for Psychology Internship: "Please describe your theoretical orientation and how this influences your approach to case conceptualization and intervention" (APPIC, 2015).…”
Section: The Proliferation Of Theoretical Orientationsmentioning
confidence: 99%
“…In the preparadigmatic era of PP, one's personally adopted theoretical orientation played a major role in informing one's understanding of the whole treatment process from the initial conceptualization of the nature and etiology of clients' problems at assessment, to the treatment plan one recommended, the treatment one provided, and how one evaluated outcomes and effectiveness at the end of treatment. This is still usually considered the standard approach for learning the profession (e.g., as reflected in the APA Competency Benchmarks [Fouad et al, 2009] and the APPIC Application for Psychology Internship [APPIC, 2015]). …”
Section: Reconciling the Unified Scientific Basis Of Psychology With mentioning
confidence: 99%
“…A first tool, questionnaire (Table 1), was designed to assess the PPP entrepreneurs project's impact on the behavioral skills of the parties involved. For the design of this questionnaire, we considered psychometric models [44], and tools to assess skills for sustainable project management [45][46][47]. This tool has already been applied to other PPPs in Spain [32], reaching a total of 613 entrepreneurs.…”
Section: Data Collection: Tools and Protocolsmentioning
confidence: 99%
“…To this end, there has been significant effort directed towards developing valid and reliable competency evaluation rating forms (CERFs). Typically, these assessment forms use Likert scales to rate trainee competence across a range of foundational (e.g., professional skills, ethical attitude and behaviour) and functional (e.g., case conceptualisation, intervention) domains (Fouad et al, 2009; Gonsalvez et al, 2015; Rodolfa, Bent, Eisman, Nelson, & Ritchie, 2005). …”
mentioning
confidence: 99%